2001
DOI: 10.1111/j.1469-7793.2001.00099.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous miniature outward currents in mechanically dissociated rat Meynert neurons

Abstract: Spontaneous miniature outward currents (SMOCs) were observed in mechanically dissociated rat Meynert neurons using nystatin perforated patch recordings under voltage‐clamp conditions. SMOCs were blocked by apamin, a selective blocker of small conductance Ca2+‐activated K+ (SK) channels, but not by blockers for other types of Ca2+‐activated K+ channel. Ryanodine (10‐100 μm) reduced both the amplitude and frequency of SMOCs. Caffeine (1 mm) increased the SMOC frequency. Blockers of the sarco/endoplasmic reticulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 36 publications
4
37
4
Order By: Relevance
“…Our previous studies demonstrated that a majority of PHN neurons fire spontaneously, whereas some PHN neurons exhibit SMOCs (Saito & Yanagawa, ; Zhang et al ., ); these outward currents display slower kinetics compared with the postsynaptic currents and are induced by Ca 2+ ‐activated K + channels, which are activated by Ca 2+ ‐induced Ca 2+ release from the endoplasmic reticulum via ryanodine receptors (Arima et al ., ; Cui et al ., ; Klement et al ., ; Saito & Yanagawa, ). In the present study, most D+ neurons (67/70) exhibited spontaneous firing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies demonstrated that a majority of PHN neurons fire spontaneously, whereas some PHN neurons exhibit SMOCs (Saito & Yanagawa, ; Zhang et al ., ); these outward currents display slower kinetics compared with the postsynaptic currents and are induced by Ca 2+ ‐activated K + channels, which are activated by Ca 2+ ‐induced Ca 2+ release from the endoplasmic reticulum via ryanodine receptors (Arima et al ., ; Cui et al ., ; Klement et al ., ; Saito & Yanagawa, ). In the present study, most D+ neurons (67/70) exhibited spontaneous firing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the association of calcium channel subtypes and ryanodine-sensitive Ca 2+ stores with Ca 2+activated K + channels differs among cell types (Marrion and Tavalin 1998;Arima et al 2001;Stocker 2004). We studied the effects of nicardipine and ryanodine on nicotine-induced ACh release.…”
Section: Effects Of Nicardipine and Ryanodine On Nicotine-induced Achmentioning
confidence: 99%
“…Indeed, this mechanism has been used to explain the generation of SMOCs in mudpuppy parasympathetic cardiac neurons (Merriam et al, 1999) and rat Meynert neurons (Arima et al, 2001). One unique property of SMOCs in DA neurons lies in the voltage dependence.…”
Section: Triggering Mechanismmentioning
confidence: 99%
“…SMOCs or SMHs are observed in various types of neurons (Brown et al, 1983;Mathers and Barker, 1984;Satin and Adams, 1987;Berridge, 1998;Seutin et al, 1998;Arima et al, 2001), as well as in smooth muscle cells, in which they are usually called spontaneous transient outward currents (STOCs) (Bolton and Imaizumi, 1996). SMOCs-STOCs are mediated by the activation of Ca 2ϩ -sensitive K ϩ channels.…”
Section: Triggering Mechanismmentioning
confidence: 99%